PERANCANGAN DAN PEMBUATAN APLIKASI KARAOKE BERBASIS WEB - Jaenudin Jaenudin; Petrus Sokibi; Rinaldi Adam (Jurnal Digit, 2018)
Abstract With the rapid development, many types of entertainment have used technology as a means to increase productivity (cost reduction and increased effectiveness) and practicality in the wearer. In today's world, karaoke activities have become a hobby for most people. Karaoke is an entertainment activity where one sings accompanied by music and lyric text shown on a monitor screen. For karaoke, it takes some audio and video equipment such as monitor and VCD / DVD player or computer that has input microphone and sound system device (amplifier and speaker) to produce good music sound. Therefore it takes a media player of the audio file that can classify the songs based on certain properties by using karaoke applications that can be used at home so it costs a little on the side of the software mostly on karaoke applications that already exist, the application only uses the features - features that can only be controlled through the desktop only, so that can only be done on one user, most people who want to karaoke usually more than one so it is not efficient for karaoke. Therefore the author will build a karaoke app that can be used offline, but has features that are almost the same as karaoke applications that are used online. So take advantage of gadgets or smartphones as a media control on karaoke applications. In this day and age everyone has been using smartphones so it has become a necessity. The use of smartphones today is not just a medium for communication but a variety of tasks can be completed. The author intends to use the smartphone and tab as a remote media karaoke applications. Unlike other karaoke applications, the software used is a VLC media player software that can be controlled with the help of PHP and HTML interface so that it can be previewed on the control device plus VLC has interface controller feature that can be made through Qt, HTML, and Lua. The author uses HTML as an interagency controller that can be run through a web browser so that control can be operated through various devices with the condition that the device has a web browser application. Keywords: Karaoke, Application, Smartphone,VLC (VideoLAN Client